ANALISIS DINAMIKA POLITIK DI BALIK TUNTUTAN PEMEKARAN CILACAP BARAT - Bisri Halim .; Kushandajani . .; wahid abdulrahman . (Journal of Politic and Government Studies, 2017)
ABSTRACTRegional splitting is a part of important things common way in any democratic countries such as Indonesia as the form and impact caused by decentralisation. Regional splitting is one of the way to increasing the public service in the purpose of creation for welfare society.The plan of regional split for west cilacap which discussed on this thesis. The writer will trying to describe how the political dynamic that occur in west cilacap regional splitt process. Start from how the political actor and organization in kabupaten Cilacap designing the plan of regional split for west cilacap could make a dynamic political constelation between them.This thesis, using a qualitative metodh with many technic such as observation and interview with many stakeholders which participating in the plan for west cilacap regional split and also using study documentation to collect some documents related to this thesis. Data analysis technique used by writer is data reduction where the writer sorting, simplifying, and transform the data obtained in the field.The results of this thesis shows the dynamics of the political forces in the District Cilacap influenced by political actors and organizations in the District Cilacap.Keyword : Regional splitting, West Cilacap, Political analysis